Volume 5A: 40th Mechanisms and Robotics Conference 2016
DOI: 10.1115/detc2016-59643
|View full text |Cite
|
Sign up to set email alerts
|

Development of Autonomous Robotic Cataract Surgery Device

Abstract: The current rate of incidence of cataracts is increasing faster than treatment capacity, and an autonomous robotic system is proposed to mitigate this by carrying out cataract surgeries. The robot is composed of a three actuator RPS parallel mechanism in series with an actuated rail mounted roller that moves around the eye, and is designed to perform a simplified version of the extracapsular cataract surgery procedure autonomously. The majority of the design work has been completed, and it is projected that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This design enables the robot to reach all parts of the eye needed to perform cataract surgery. The study showed that sub‐millimetre accuracy is sufficient for cataract surgery 69 …”
Section: Background and Current State Of Robotic Eye Surgerymentioning
confidence: 94%
“…This design enables the robot to reach all parts of the eye needed to perform cataract surgery. The study showed that sub‐millimetre accuracy is sufficient for cataract surgery 69 …”
Section: Background and Current State Of Robotic Eye Surgerymentioning
confidence: 94%
“…It is reported that a precision of 500 microns about an RCM point on the surface of the incision are required for robot-assisted cataract surgery [16]. Considering the potential applications on vitreoretinal surgery, the robot proposed in the herein paper aims to achieve a precision of 10 microns [17].…”
Section: B Specification Of the Robotmentioning
confidence: 99%